2003
DOI: 10.1111/j.1752-1688.2003.tb04399.x
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT OF VARIED DATA RESOLUTION ON HYDRAULIC MODELING AND FLOODPLAIN DELINEATION1

Abstract: Current data collection technologies such as light detection and ranging (LIDAR) produce dense digital terrain data that result in more accurate digital terrain models (DTMs) for engineering applications. However, such data are redundant and often cumbersome for hydrologic and hydraulic modeling purposes. Data filtering provides a means of eliminating redundant points and facilitates model preparation. This paper demonstrates the impact of varied data resolution on a case study completed for a 2.3 mi2 area wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 1 publication
0
40
0
2
Order By: Relevance
“…After the integration of a scanning mechanism with lidar and an inertial measurements unit with GPS in the early 1990s, it has been possible to use first airborne laser scanning (ALS), then MLS data, in addition to static based terrestrial laser scanning (TLS), to improve the measurement and modeling of fluvial environments (e.g., [2][3][4][5][6][7][8][9][10][11][12]). High-resolution ALS provides detailed information on topographical features of fluvial environments that influence the river hydraulics, giving, therefore, the potential to improve existing hydraulic models (e.g., [13][14][15][16][17]). Furthermore, TLS can be applied to measure the grain-scale surface roughness needed in river flow modeling.…”
Section: Introductionmentioning
confidence: 99%
“…After the integration of a scanning mechanism with lidar and an inertial measurements unit with GPS in the early 1990s, it has been possible to use first airborne laser scanning (ALS), then MLS data, in addition to static based terrestrial laser scanning (TLS), to improve the measurement and modeling of fluvial environments (e.g., [2][3][4][5][6][7][8][9][10][11][12]). High-resolution ALS provides detailed information on topographical features of fluvial environments that influence the river hydraulics, giving, therefore, the potential to improve existing hydraulic models (e.g., [13][14][15][16][17]). Furthermore, TLS can be applied to measure the grain-scale surface roughness needed in river flow modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of interest to see how much the original laser data can be filtered, without losing predictability performance. For an area around Leith Creek, North Carolina, Omer et al (2003) looked at the angle a between two surveyed data points (Fig. 1).…”
Section: Previous Research On Delineation Uncertainties Related To Demsmentioning
confidence: 99%
“…1 Angle used to determine if point should be filtered away or kept in the DEM (cf. Omer et al 2003) surveyed data, 5 m contour data (scale 1:5000), as well as combinations between them, together with or without bathymetric data. They concluded that for a 500 m 3 /s discharge, the 4 m resolution DEM yielded inundated area differences up to 7.3 %.…”
Section: Previous Research On Delineation Uncertainties Related To Demsmentioning
confidence: 99%
“…The areas with water depth greater than zero are considered to be flooded (Merwade, 2012;Noman et al, 2001;Omer et al, 2003;Tate et al, 2002). …”
Section: Creation Of Flood Mapsmentioning
confidence: 99%
“…Resolutions of DEMs can affect the parameters and attributes derived from them and influence models associated with them (Gallant & Hutchinson, 1997;Haile & Rientjes, 2005;Omer et al, 2003). The vertical accuracy of a DEM is the probability distribution of digital elevation values measured with respect to the true value.…”
mentioning
confidence: 99%